Prevalence of Pancreatic Cystic Lesions Is Associated With Diabetes Mellitus and Obesity: An Analysis of 5296 Individuals Who Underwent a Preventive Medical Examination. Issue 6 (July 2017) - Mizuno, Suguru; Isayama, Hiroyuki; Nakai, Yousuke; Yoshikawa, Takeharu; Ishigaki, Kazunaga; Matsubara, Saburo; Yamamoto, Natsuyo; Ijichi, Hideaki; Tateishi, Keisuke; Tada, Minoru; Hayashi, Naoto; Koike, Kazuhiko
Abstract : Objectives: Pancreatic cystic lesions (PCLs) are considered precursors of pancreatic cancer. Diabetes mellitus (DM) and obesity are known as risk factors for pancreatic cancer. We investigated the prevalence of PCLs in the general population and the relationship between PCLs and DM/obesity. Methods: This cross-sectional analysis included 5296 individuals who underwent a preventive medical examination between October 2006 and June 2013 at our institution. Magnetic resonance imaging, including magnetic resonance cholangiopancreatography, was performed using a 3.0-T system as part of a comprehensive health screening program. We investigated the prevalence and risk factors of PCLs. Results: The prevalence of PCLs was 13.7%, which was increased according to age. Individuals with PCLs were more prone to obesity (body mass index, 24.0 vs 23.7 kg/m 2 [ P = 0.015]; waist circumference, 87.4 vs 85.5 cm [ P < 0.001]). DM was more prevalent in individuals with PCLs (18.4% vs 10.5%, P < 0.001). In a multivariate analysis, age (odds ratio [OR], 1.06; P < 0.001), excess body mass index (OR, 1.26; P = 0.039), and DM (OR, 1.39; P = 0.005) were associated with PCLs. Conclusions: The prevalence of PCLs detected by magnetic resonance imaging in a preventive medical examination was 13.7%. Pancreatic cystic lesions were significantly associated with DM and obesity.